KARAKTERISASI FISIKO KIMIA DAN INHIBISI α-GLUKOSIDASE BERAS ANALOG DARI BUAH Rhizophora mucronata [CHARACTERIZATION OF PHYSICO-CHEMICAL AND α-GLUKOSIDASE INHIBITION OF ANALOG RICE FROM Rhizophora mucronata FRUIT] - Hardoko Hardoko; Devy Alfiana; Yunita E. Puspitasari (Universitas Pelita Harapan, 2019)
This study aims to determine the physicochemical characteristics and α-glucosidase inhibition of analog rice from R. mucronata fruit flour, cassava flour, and E. cottonii flour. This research was conducted in April - October 2016. The experimental method was through the treatment ratio of R. mucronata fruit flour with cassava flour (60:40, 70:30, 80:20) and addition of E. cottonii flour (0, 3, 5, 7 %). Making analog rice using an extruder. The results showed that the treatment ratio of R. mucronata fruit flour with cassava flour and the addition of E. cottonii flour had a significant positive effect on α-glucosidase inhibition and physicochemical properties of rice. The higher the amount of R. mucronata fruit flour used the higher inhibition activity of αglucosidase and decrease the IC value. The best analog rice is made from R. mucronata 60% fruit flour, 40% cassava flour, and 5% E. cottonii seaweed flour. This rice has IC 50 value of 33.42 ppm, water content of 8.46%, food fiber content of 38.96%, red color (oHue value of 44.86), cooking time of 11.35 minutes, development volume of 135.09%, and starch content of 51.44%. ABSTRAKPenelitian ini untuk mengetahui karakteristik fisiko kimia dan inhibisi α-glukosidase beras analog dari tepung buah R. mucronata, tepung singkong, dan tepung E. cottonii. Penelitian ini dilaksanakan pada bulan April - Oktober 2016. Metode eksperimen melalui perlakuan rasio tepungbuah R. mucronata dengan Tepung singkong (60:40, 70:30, 80:20) dan penambahan tepung E. cottonii (0, 3, 5, 7%). Pembuatan beras analog menggunakan extruder. Hasilnya menunjukkan bahwa perlakuan rasio tepung buah R. mucronata dengan tepung singkong dan penambahan tepung E. cottonii berpengaruh posistif nyata terhadap inhibisi α-glukosidase dan sifat fisiko kimia beras. Semakin tinggi jumlah tepung buah R. mucronata yang digunakan makin tinggi aktivitas inhibisi αglukosidase dan menurunkan nilai IC. Beras analog terbaik adalah yang terbuat dari tepung buah R. mucronata 60%, tepung singkong 40%, dan tepung rumput laut E. cottonii 5%. Beras ini mempunyai nilai IC 50, 33,42 ppm, kadar air 8,46%, kadar serat pangan 38,96%, berwarna merah (nilai o Hue 44,86), cooking time 11,35 menit, volume pengembangan 135,09%, dan kadar pati 51,44%. Kata Kunci : beras analog, α-glukosidase, IC50, R. mucronata